Human enteroviruses isolated during acute flaccid paralysis surveillance in Ghana: Implications for the post eradication era - Odoom, J.K.; Obodai, E.; Barnor, J.S.; Ashun, M.; Arthur-Quarm, J.; Osei-Kwasi, M. (Pan African Medical Journal, 2012)
Surveillance of acute flaccid surveillance (AFP) has been used world-wide to monitor the control and eradication of circulating wild polioviruses. The Polio Laboratory since its accreditation in 1996 has supported the Disease Surveillance Department for AFP surveillance. This study aims to isolate and characterize human enteroviruses from patients with AFP in Ghana. Method: Stool suspension was prepared from 308 samples received in 2009 from the surveillance activities throughout the country and inoculated on both RD and L20B cell lines. Isolates that showed growth on L20B were selected for real-time RT-PCR using degenerate and non-degenerate primers and probes. RD isolates were however characterized by microneutralisation technique with antisera pools from RIVM, The Netherlands and viruses that were untypable subjected to neutralization assay using antibodies specific for E71. Results: Of the 308 samples processed, 17 (5.5%) grew on both L20B and RD cells while 32 (10.4%) grew on RD only. All 28 isolates from L20B were characterized by rRT-PCR as Sabin-like polioviruses. No wild poliovirus or VDPV was found. However from the microneutralisation assay, six different enteroviruses were characterized. Among these, Coxsackie B viruses were most predominant followed by Echovirus. Three children from whom non-polio enteroviruses were isolated had residual paralysis while one child with VAPP found. The non-polio enteroviruses circulated throughout the country with the majority (20.7%) from Ashanti region. Conclusion: This study showed the absence of wild or vaccine-derived poliovirus circulation in the country. However, the detection of three non-polio enteroviruses and one Sabin-like poliovirus with residual paralysis call for continuous surveillance even in the post polio eradication era.
Keywords: Acute flaccid paralysis; Ghana; Non-polio enterovirus; Poliovirus; Surveillance